Universal exciton size in organic polymers is determined by nonlocal orbital exchange in time-dependent density functional theory - Mewes, Stefanie; Plasser, Felix; Dreuw, Andreas (The journal of physical chemistry letters, 2017)
The exciton size of the lowest singlet excited state in a diverse set of organic π-conjugated polymers is studied and found to be a universal, system-independent quantity of approximately 7 Å in the single-chain picture. With time-dependent density functional theory (TDDFT), its value as well as the overall description of the exciton is almost exclusively governed by the amount of nonlocal orbital exchange. This is traced back to the lack of the Coulomb attraction between the electron and hole quasiparticles in pure TDDFT, which is reintroduced only with the admixture of nonlocal orbital exchange.